1994
DOI: 10.1103/physreve.49.4627
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects in a nonlinear model of monolayer Scheibe aggregates

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 33 publications
0
100
0
Order By: Relevance
“…Another example of NLS equation with noise is given in [1] and [2], where it describes energy transfer in monolayer molecular aggregates, and where the noise stands for thermal fluctuations. As explained in [2], this noise may be multiplicative if it describes process where excitation is not being created or destroyed and in this case the noise appears in the equation as a linear potential.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of NLS equation with noise is given in [1] and [2], where it describes energy transfer in monolayer molecular aggregates, and where the noise stands for thermal fluctuations. As explained in [2], this noise may be multiplicative if it describes process where excitation is not being created or destroyed and in this case the noise appears in the equation as a linear potential.…”
Section: Introductionmentioning
confidence: 99%
“…This is to be expected, since those discrete systems are effectively discretizations of SNLS with noise of spatial correlation on length scale comparable to the mesh spacing of the discretization. The full 2D Stochastic NLS equation with spatially uncorrelated noise has been simulated by Bang, Christiansen, If, Rasmussen and Gaididei in [1], and the 1D quintic case of the Stochastic NLS equation by DeBussche and Di Menza in [9]. In each case it is observed that spatially uncorrelated noise above a certain threshold level prevents wave collapse.…”
Section: 7mentioning
confidence: 99%
“…An exciton-phonon system with phase noise and damping. Such thin films can be modeled as an exciton-phonon system with noise and damping acting on the internal modes as described by Bang, Christiansen, If, Rasmussen and Gaididei in [1], which adds damping to the purely quantum mechanical modeling of Bartnick and Tuszyński [2]:…”
Section: Introductionmentioning
confidence: 99%
“…14 Since the 2D DNLS equation also has been used to describe exciton dynamics in models for so-called Scheibe aggregates in molecular thin films, 15,16 the discrete breathers may be of importance also in this context.…”
Section: Introductionmentioning
confidence: 99%